Labor Market Adjustments to Shocks in Australia - Mohommad, Adil (IMF Working Papers; Working Paper ;, 2017)
Labor markets in Australia have adjusted smoothly to significant declines in commodity prices with little increase in unemployment. This paper examines several aspects of the adjustment, focusing on (i) evidence of increased labor market frictions following the commodity price decline; (ii) flexibility in labor input adjustment in response to demand shocks; (iii) changes in labor productivity in the wake of resource reallocation with the decline in mining investment, (iv) and the role of migration in adjusting to the commodity price and mining investment cycle. We find little evidence of increased labor market frictions with the decline in commodity prices. The relatively smooth transition has been assisted by increased flexibility in adjustment of worker hours over time. Labor productivity growth has sustained its historical average through the transition, despite some temporary drag as the economy rebalances. Finally, migration has played a key role in labor market adjustment through the commodity cycle.